2012
DOI: 10.3892/mmr.2015.3505
|View full text |Cite
|
Sign up to set email alerts
|

DNA-dependent protein kinase catalytic subunit inhibitor reverses acquired radioresistance in lung adenocarcinoma by suppressing DNA repair

Abstract: Abstract. The mechanisms underlying lung cancer radioresistance remain to be fully elucidated. The DNA repair pathway is a predominant target of radiotherapy, which is considered to be involved in the acquired radioresistance of cancer cells. The present study aimed to establish a radioresistant cell model using the A549 human lung cancer cell line, and to further investigate the potential mechanisms underlying the radioresistance. The A549R radioresistant lung cancer cell variant was established by exposing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, lung adenocarcinoma is not highly sensitive to radiation, and the progressive tolerance of tumor cells during irradiation often causes local recurrence and poor prognosis [5]. Because the sensitivity of tumor cells is a key factor in the efficacy of radiotherapy, it is necessary to identify critical molecules related to the radiosensitivity of lung adenocarcinoma, as well as the factors linked to rapid cell growth.…”
Section: Ivyspringmentioning
confidence: 99%
“…However, lung adenocarcinoma is not highly sensitive to radiation, and the progressive tolerance of tumor cells during irradiation often causes local recurrence and poor prognosis [5]. Because the sensitivity of tumor cells is a key factor in the efficacy of radiotherapy, it is necessary to identify critical molecules related to the radiosensitivity of lung adenocarcinoma, as well as the factors linked to rapid cell growth.…”
Section: Ivyspringmentioning
confidence: 99%
“…An analysis of a previous meta-analysis reported that postoperative chest radiotherapy has an overall negative effect on survival, resulting in a 21.3% relative increase in odds of dying [hazard ratio (HR)1.21 (95% CI 1.08-1.34)]; meaning, an absolute reduction of 7% in survival from 55% to 48% at 2 years owing to the decrease in survival rates possible (43, 44). One of the possible reasons for this finding may be the increase in intrinsic and acquired radioresistance among patients suffering from cancers, which has led to a decrease in the success of their treatment (45).LUAD is not particularly sensitive to radiation, and thus, tumor cells are capable of developing a tolerance to radiation, resulting in local recurrences and poor prognoses (46).…”
mentioning
confidence: 99%
“…As one of mainstream cancer therapies, RT has a good effect in a variety of tumors ( De Ruysscher et al, 2019 ; Sia et al, 2020 ). However, it is not so effective for several cancers, including LUAD ( Li et al, 2015 ). In the clinic, there are many NSCLC patients who are failed to achieve a cure after surgery.…”
Section: Discussionmentioning
confidence: 99%